EFFECT OF PEGYLATED POLYPROPYLENE IMINE DENDRITIC ARCHITECTURE ON PHARMACOKINETICS OF PYRAZINAMIDE ON RABBITS - BALASUBRAMANIAN, ARUL; BALASUBRAMANIAN, VALLI MANALAN; RAMALINGAM, KOTHAI (International Journal of Applied Pharmaceutics, 2024)
Objective: This study sought to investigate the impact of pegylated polypropylene imine dendrimer-loaded pyrazinamide on drug delivery and assess this novel formulation's pharmacokinetic parameters. Methods: Various concentrations of pyrazinamide-loaded dendrimers were formulated in four distinct batches, with the most promising formulation selected for administration to New Zealand rabbits. Plasma concentrations of the drug were subsequently compared to those of the pure drug. Pharmacokinetic parameters, including maximum plasma concentration (Cmax), time to reach Cmax (tmax), the area under the curve (AUC), the area under the first moment curve (AUMC), elimination rate constant (λz), biological half-life (t1/2), and mean residence time (MRT), were meticulously determined. Results: The plasma drug concentration Vs time profile illustrated a sustained release pattern for the pyrazinamide drug-loaded dendrimer formulation compared to the pure drug. While a minor alteration was observed in peak plasma concentration, a notable divergence was noted in all other pharmacokinetic parameters. The AUC demonstrated a fourfold increase for pyrazinamide drug-loaded dendrimers, rising from 8657.94±295.10 to 34663.89±702.89 (ng/ml/h), and the mean residence time nearly doubled when compared to the pure drug. Conclusion: Pyrazinamide drug-loaded dendrimers exhibit significant potential for enhancing drug release compared to the pure drug. This novel formulation promises a substantial and sustained drug release profile, holding promise for improving therapeutic outcomes and patient compliance in the treatment of relevant conditions.